Single cell RNA-seq analysis of lymphocytes from Borrelia burgdorferi infected mice - Rinne, Varpu (My University, 2022)
Lyme borreliosis is a disease caused by Borrelia burgdorferi sensu lato bacteria. The symptoms of disseminated Lyme borreliosis can be nonspecific, and there is a need for specific laboratory tests. Currently, the laboratory diagnostics of Lyme borreliosis is mainly based on the serology, which is of no use in the early infection or in the case of a suspected re-infection. Single cell RNA sequencing (RNA-seq) is a technique used to analyse the whole transcriptome profile of biological samples at a single cell level. The aim of this study was to identify possible differences in lymph node lymphocytes in B. burgdorferi infected and control mice using single cell RNA-sequencing technology. Two groups of mice, four each, (C3H/He, age 4 weeks) were used. One group was infected with B. burgdorferi (strain N40) and the other with buffer (control group). The infection was allowed to proceed for four days. Lymph nodes from mice were processed to isolate lymphocytes, and the cells were processed to single cell RNA-seq analysis. R programming language were used for the bioinformatic analysis. With single cell RNA-seq analysis, differences could be identified between these two conditions. Increased amount of B cells, plasma cells and plasma blast and the lack of CD4+ T helper cells, except T H1 cells was notable in the infection group. This may support the role of B cells in antigen presentation and antibody production with help of TH1 cells in acute B. burgdorferi infection. These results might suggest that B cell immune responses associated with B. burgdorferi infection may be detectable to support Lyme borreliosis diagnostics. Further studies are needed to confirm the specificity of the finding with Lyme borreliosis.
Keywords: Borrelia burgdorferi, Lymphocyte, Single cell RNA-seq analysis, Lyme borreliosis, Bioinformatic